Pendampingan Psikologis Menumbuhkan Sikap Self-Compassion pada Siswa - Rosyidah, Hani; Setiawati, Rini; Nugrahaeni, Dwitiya Ari; Lestari, Ayu; Warokhmah, Welda Nastiti; Azzahra, Alya Zalfa (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This psychological support program aims to help early adolescents develop self-compassion skills as they navigate the challenges of transition. Comparing oneself to others and evaluating one's own abilities can cause adolescents to lose confidence and doubt themselves. The program involved identifying needs, administering a pretest, providing materials, facilitating discussions, conducting practical exercises that covered basic self-compassion concepts, and administering a posttest. The program's results showed an increase in self-compassion understanding among 57 SMA 2 Muhammadiyah Magelang students. Students provided positive feedback about the program because they found it relevant to their experiences and wanted it to be longer. It can be concluded that the self-compassion counseling program was successful because it increased participants' understanding of self-compassion. It also provided knowledge of effective strategies for promoting sustainable well-being.